ANALISIS PSIKOLOGI TOKOH UTAMA MASAKO DALAM NOVEL OUT KARYA NATSUO KIRINO - Istri Arimas, I Gusti (Humanis; Volume 8. No. 2. Agustus 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This thesis was entitled "An Analysis Psychology Of The Main Character Masako In The Novel Out by Natsuo Kirino". The data source used in this study is an original Japan novel titled Out by Natsuo Kirino. The study used descriptive analysis and formal method. The Conflict analysis using theory from Stanton. The analysis of the psychology of the main character using the theory of psychoanalysis from Sigmund Freud. Sigmund Freud's theory of psychoanalysis consists of three basic personality system i.e. id, ego and superego. The results of analysis showed existence of conflicts that plagued Masako figures there are two points, internal conflict and external conflict. Psychology analysis results showed that the psychology of Masako is dominated by id because she always follows her desire without thinking about the impact that occurs. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: the main character, conflict, psychology, psychoanalysis